Pengaruh Aplikasi Formula Pantoea agglomerans Terhadap Aktivitas Antioksidan dan Kandungan Klorofil Daun Tanaman Strowberi - PHABIOLA, TRISNA AGUNG; KHALIMI, KHAMDAN (Agrotrop : Journal on Agriculture Science; Vol 2 No 2 (2012), 2014)
The objectives of this experiment were conducted to evaluate the effectiveness of Pantoea agglomerans formulations to increase antioxidant activities and chlorophyll content of strawberry plants. P. agglomerans was formulated in the forms of gel and powder. Measurement of peroxidase activity carried out 7 days after application of P. agglomerans formulations on strawberry plants. The manner in which the Cohen prosedure suggested by Simon and Rose (1970) and has been modified. Total chlorophyll content (SPAD unit) was determined with a chlorophyll-meter SPAD-502. Some growth parameters were observed such as plant height, number of leaves, and leaf area. Results of this study showed that application of P. agglomerans formulations could increase the peroxidase activity. Peroxidase activity on treated plants increased by 47.17% to 50.16% in comparison with un-treated plants. Total chlorophyll content on treated plants increased by 23.81% to 28.22% in comparison with un-treated plants. These results suggested that application of P. agglomerans formulations could increase the total chlorophyll content and antioxidant activity of strawberry plants.
Keywords: P. agglomerans formulations, chlorophyll content, antioxidant activity